Формирование технического облика саук агрегата подачи воды паровых котлов - Коваль, Вячеслав Алексеевич; Валюхов, С. Г.; Ярославцев, С. В. (Eastern-European Journal of Enterprise Technologies, 2009)
The purpose of the given work is formation of shape and synthesis of laws of regulation SAUK of pressure of water «after itself» on the transitive operating modes providing their optimization at set ranges of levels of constant indignations. The system of automatic control represents a regulator of an output. Problems of construction of observers in the given work are not mentioned